Analisis tingkat kecemasan ibu terhadap milestone pada anak - Panghesti Cahya Utami; Fijriani Fijriani; Christine Masada Hirashita Tobing (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
The purpose of this study was to determine the anxiety level analysis of a mother on child milestone at Posyandu. The research method used in collecting information is the qualitative method, in the form of real information and what it is when the research is carried out. The informants of this research were the members of the Posyandu, in determining the number of research informants, the author uses the Purposive Sampling technique, with a total of five members of the Posyandu. The instruments used are observation guidelines, interviews, and documentation studies. Observation intended for observing the condition of mothers and children in their neighborhood, interviews are addressed to mothers of Posyandu members. The data analysis technique is done by reducing the data according to the informant’s answers when conducting interviews, next step is to display the data, which is to briefly describe the results of the interview, then make conclusions from each interview and observation results. The conclusions and results of the study indicate that the level of anxiety of a mother against milestones in children is in the medium category.